The future's bright but the future's local – the rise of hyperlocal journalism in the United Kingdom. (1st March 2017) - White, Douglas; Pennycook, Lauren; Perrin, William; Hartley, Sarah
Good-quality local journalism, which investigates and reports on politics, business, planning, crime and social issues, is a long-established, critical function of a healthy and thriving local democracy. Reports on local events, stories, achievements and personalities are vital to citizens' sense of their community and place. However, the UK market for local news has changed beyond recognition in recent years. Four in ten adults in the United Kingdom now use online sources for local news, while half of local news consumers rely on the Internet even more frequently today than they did only two years ago. Traditional business models have been under extreme pressure in this new digital age. Local newspapers are now adapting to these new circumstances and have adapted a variety of different approaches to try and build viable business models in this new age. Clearly the local newspaper industry will continue to play a vital role in the ecosystem of local news. At the same time, however, a new 'hyperlocal' news sector is emerging, helping to fill gaps in local media provision and adding significantly to local media plurality. This article discusses the opportunities and challenges facing hyperlocal news in the United Kingdom. and explores the potential for the growth of the new media form of microlocal journalism. This article is written by Douglas White and Lauren Pennycook at the Carnegie UK Trust, a charitable trust that developed a £50, 000 competition to improve local news reporting, and William Perrin and Sarah Harley from Talk About Local, who evaluated the project. The article is based on the final report of the Neighbourhood News project, 'The Future's Bright, the Future's Local', published by the Carnegie UK Trust in December 2014.